Green transformational leadership, environmental performance, dan green creativity: Peran pro-environmental behavior - Utik Bidayati (Jurnal Mirai Management, 2026)
The rising demand for sustainable business practices is pushing organisations to reduce their environmental impact while developing innovative solutions that support sustainability. This study examines the positive influence of green transformational leadership on environmental performance and green creativity, with pro-environmental behavior as a mediating variable. The research uses a quantitative approach and data were collected through questionnaires distributed to 160 respondents selected using purposive sampling. The data were analysed using Smart PLS 4.0 for validity, reliability, and hypothesis testing. The results show that green transformational leadership has a positive effect on pro-environmental behavior, environmental performance, and green creativity. Pro-environmental behavior positively affects environmental performance and green creativity and also proves to be a partial mediator linking green transformational leadership with both variables. This study contributes by integrating social learning theory and ability-motivation-opportunity theory to explain organisational environmental outcomes.